Determination of Radon Exhalation Rates from Tiles (Marble, Granite and Ceramic) Using LR115 Type II Passive Technique - H Bakr (University of Thi-Qar Journal of Science, 2019)
Exhalation of 222Rn, α-radioactive inert gas, is associated with the presence of 226Ra andit's ultimate precursor uranium in the earth crust. It is a useful quantity to compare the relativeimportance of different materials of tiles (marble, granite and ceramic). Majority of newhouses in Basrah (Iraq) are using tiles. Therefore, studies concerning the determination ofradon exhalation rate from there materials were carried out using LR-115 Type ІІ passivetechnique in this content, the Solid State Nuclear Track Detectors(SSNTDs) with a plasticcontainer('can' technique) were applied .There container were hermetically sealed and storedfor 120 days to attain equilibrium between 222Rn and 226Ra . After exposure to radon, LR115type II detectors were etched in 2.5N NaOH solution at 60°C for 2h. From the measured radonconcentration values , 222Rn exhalation rates were determined. The average values ofexhalation rates for radon has been found of values ( 0.225, 1.529, 16.196 Bq m-2 h-1) formarble, ceramic and granite respectively. Exhalation rates for granite has been found to beseveral times higher than that for marble and ceramic. The results of the measurement hasbeen discussed.